3D PCDM Probabilistic Shaping Transmission Scheme Based on Chaotic Constellation Mapping - Mengjie Wu; Bo Liu; Jianxin Ren; Yu Bai; Zeqian Guo; Shuyu Zhou; Yilan Ma; Gengyin Chen; Yongyi Yu; Xiangyu Wu; Yaya Mao; Feng Wang; et al. (IEEE Photonics Journal, 2023)
In this article, a high-security three-dimensional (3D) probabilistic shaping optical transmission system based on prefix-free code distribution matching (PCDM) and Polar code joint coding is proposed. The bit error rate (BER) performance of the communication system is optimized by using the probabilistic shaping effect of PCDM and the strong correction performance of Polar code. Meantime the Logistic and Lorenz chaotic models are used to mask the constellation map for multiple times to ensure the security transmission of data. The experiment verifies the transmission of 28.64Gb/s encrypted PCDM encoded signals on 2km 7-core fiber. At a BER is 1×10-3, the encrypted PCDM encoded signals improve the BER performance about 3dB compared to the conventional unencrypted 3D 32QAM signals. In terms of security performance, the key space of the proposed encryption scheme is up to 10119, and the BER of the illegal receiver is more than 0.4. The experimental results show that the proposed chaotic optical transmission scheme based on the joint encoding of PCDM and Polar can effectively improve the BER and security performance, which is a promising optical communication transmission scheme.